Seleção de marcadores ISSR (Inter Simple Sequence Repeat) para o estudo da diversidade genética em Euphorbia heterophylla L - Silva, Débora da (2014)
The species Euphorbia heterophylla L., popularly known as milkweed (amendoim-bravo and leiteiro in Brazil), is one of the most important weeds in soybean culture and affects the productivity of many annual and perennial crops in several countries. Studies on the species are especially due to its frequent invading factor in economically important crops such as soybeans, corn and sugar cane. The assessment of genetic diversity and knowledge of population genetics structure are important factors to identify types of management and to guide the development of effective planning in weed control. Owing to the relevance of the weed control, current study standardized reactions and selected ISSR markers to assess the genetic diversity in 132 samples of Euphorbia harvested in eight regions of the state of Paraná, Brazil, and a single region of the state of Rio Grande do Sul, and of the state of São Paulo, Brazil, to investigate how these populations were genetically structured. In a total of 132 samples of E. heterophylla, thirty ISSR primers were evaluated and only nine had their DNA amplified. A wide genetic diversity was reported at population level; average polymorphic ISSR sequences was 98.50%, with highest rates in plants collected in Pato Branco II (87.97%) and with lowest rates in plants collected in Pato Branco I (33.83%), both in the state of Paraná. Ney´s genetic diversity (He) and Shannon´s index ranged between 0.1335 and 0.3800 and between 0.1948 and 0.5462, respectively. The above showed that the samples of milkweed analyzed are genetically divergent. Total diversity (Ht) for all plants collected from 10 sites was 0.3611, whilst the level of genetic divergence (GST) was high (0.3607). Since high total diversity and differentiation coefficient rates demonstrated the great variation for some ISSR segments, this fact indicated that the samples collected in different regions comprised genetically divergent samples. Polymorphism analysis with Bayesian statistics indicated that plants from the 10 localities were grouped into six ancestral groups. Some samples showed a predominance of groups of alleles and other shared alleles with five or six groups. The above provided a high molecular variance within the samples evaluated. The same result was also given by the AMOVA analysis, which indicated that 68% of the total genetic variation occurred in the samples, whereas the variation between samples reached 32%. The identity and genetic similarity rates estimated by the UPGMA grouping method showed that samples Jandaia I and Jandaia II were the most similar (I = 0.9416), and the samples of Pato Branco I and Pato Branco III were the most divergent (I = 0.6915). The samples evaluated formed a large group, with the exception of sample from Pato Branco III. The estimated genetic identity rates ranged between 0.6915 and 0.9416, and indicated a broad genetic base for the ten E. heterophylla samples collected. Results show that genetic divergence is independent of geographic distance. Consequently, samples of milkweed analyzed in current study with high genetic diversity at the molecular level may be founder populations containing different ISSR markers and forming genetically structured populations. The nine ISSR markers identified in current analysis may be used to monitor effects of types and/or different doses of herbicides on the milkweed genome and as determinant or non-determinant factors of E. heterophylla population structure.